Experimental study on pulsation frequency of free-, wall- and corner buoyant turbulent diffusion flames. (15th September 2020) - Zhang, Xiaolei; Fang, Xu; Miao, Yanli; Hu, Longhua
Highlights: Flame pulsation frequencies of free-, wall- and corner buoyant flames quantified. Effect of wall on flame pulsation frequency revealed. Correlation for flame pulsation frequency established. Characteristic length scale for the flame pulsation frequency proposed. Abstract: This work studies the flame pulsation frequency f of free-, wall- and corner buoyant turbulent diffusion flames. Five square gaseous burners with the burner side length of 10, 15, 20, 25 and 30 cm are used to produce the three types of flames. In addition, five rectangular gaseous burners with dimensions of 30 cm × 15 cm, 25 cm × 12.5 cm, 20 cm × 10 cm, 15 cm × 7.5 cm, 10 cm × 5 cm (aspect ratio of 2:1 with half surface area of the square burners) are also used to produce wall flames. Propane is used as fuel. Results show that heat release rates have no significant effect on f . The flame pulsation frequency of free flames is larger than that of wall flames, which is further larger than that of corner flames. For all types of flames, the flame pulsation frequency decreases with the increasing of the burner size. The classic 1/2 power law correlation, i.e., f ( g / D ) 0.5 for flame pulsation frequency of free flame can well describe the data of all types of flames (square, rectangular; free flame, wall flame and corner flame) on the basis of the "mirror" approach, and the perimeter-equivalent diameter is used as the appropriate length scale.